(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to provide an overview and explanation of public service innovations in the process of making birth certificates and death certificates at the Makassar City Population and Civil Registry Service. This study used the type of qualitative descriptive research. Data collection instruments were interviews with informants verbally and structured interviews, such as observations at the research location and also based on documents in the form of literature, documents, tables and scientific papers available at institutions associated with research. The results of this study showed that KUCATAKI Service Innovation in making birth certificates and death certificates in the Population and Civil Registry Service of Makassar City was good and fully oriented to the wishes of the community namely easy service and the community did not feel difficulties in matters maintenance of certificates, and especially pregnant women who wanted to manage of their child’s birth certificate directly at the RSIA/ Puskesmas where they got birth.